The history of ancient Israel: a guide for the perplexed - Davies, Philip R. (Guides for the perplexed, 2015)
"The History of Ancient Israel: A Guide for the Perplexed provides the student with the perfect guide to why and how the history of this most contested region has been studies, and why it continues to be studied today. Philip R. Davies, one of the leading scholars of Ancient Israel in recent years, begins by examining the relevance of the study of Ancient Israel, giving an overview of the sources and issues facing historians in approaching the material. Davies then continues by looking at the various theories and hypotheses that scholars have advanced throughout the 20th century, showing how different approaches are presented and in some cases how they are both underpinned and undermined by a range of ideological perspectives. Davies also explains the rise and fall of Biblical Archaeology, the 'maximalist/minimalist' debate. After this helpful survey of past methodologies Davies introduces readers to the current trends in biblical scholarship in the present day, covering areas such as cultural memory, the impact of literary and social scientific theory, and the notion of 'invented history'. Finally, Davies considers the big question: how the various sources of knowledge can be combined to write a modern history that combines and accounts for all the data available, in a meaningful way. This new guide will be a must for students of the Hebrew Bible/Old Testament."--